A 3D Microscaffold Cochlear Electrode Array for Steroid Elution. Issue 20 (18th September 2019) - Jang, Jongmoon; Kim, Jin‐young; Kim, Yeong Cheol; Kim, Sangwon; Chou, Namsun; Lee, Seungmin; Choung, Yun‐Hoon; Kim, Sohee; Brugger, Juergen; Choi, Hongsoo; Jang, Jeong Hun
Abstract: In cochlear implants, the electrode insertion trauma during surgery can cause damage residual hearing. Preserving the residual hearing is an important challenge and the localized administration of drugs, such as steroids, is one of the most promising ways, but remains a challenge. Here, a microscaffold cochlear electrode array (MiSCEA) consisting of a microfabricated flexible electrode array and a 3D microscaffold for steroid reservoir is reported. The MiSCEA without loaded drug is tested by measuring the electrically evoked auditory brainstem response of the cochlea in guinea pigs ( n = 4). The scaffold is then coated with steroid (dexamethasone) encapsulated in polylactic‐ co ‐glycolic acid and the continuous release of the steroid into artificial perilymph during six weeks is monitored. The steroid‐containing scaffolds are then implanted into guinea pigs ( n = 4) and threshold shifts are analyzed for four weeks by measuring the acoustically evoked auditory brainstem response. The threshold shifts tend to be lower in the group implanted with the steroid‐containing MiSCEAs. The feasibility of 3D MiSCEA opens up the development of potential next‐generation cochlear electrode with improved steroid release dynamics into cochlea. Abstract : A microscaffold cochlear electrode array (MiSCEA) consisting of a microfabricated flexible electrode array and a 3D microscaffold for steroid reservoir is developed. The MiSCEA coating steroid (dexamethasone) encapsulated in polylactic‐ co ‐glycolic acid is implanted into cochlea of guinea pigs and the hearing threshold shifts after four weeks tend to be lower than the MiSCEA without coating steroid.